The The Evidentiary Value of Visum et Repertum in Establishing the Crime of Attempted Rape (An Analysis of Court Decision No. 72/Pid.B/2021/PN.Pps) - Rania Adriane Desrina Rania; Handar Subhandi Bakhtiar Handar (Dinasti Research, 2026)
Evidence plays a central role in criminal law, as Article 184 of the Criminal Procedure Code establishes it as the basis for judges to determine whether the elements of a crime are proven lawfully and convincingly. In the case of attempted rape against a deaf and mute person with disabilities in Decision Number 72/Pid.B/2021/PN.Pps, the evidentiary process faced challenges due to the victim’s limited communication. This study aims to analyze the role of visum et repertum in proving the elements of attempted rape. Using a normative juridical method with a case approach, this research relies on legislation and court decisions as primary materials, supported by scholarly works. The results show that visum et repertum is written evidence with strong probative value, as it presents objective medical findings indicating physical violence, supporting the elements under Article 285 in conjunction with Article 53 paragraph (1) of the Criminal Code. In this case, visum et repertum strengthened witness testimonies and helped the judge form a conviction that acts leading to rape had occurred, despite no intercourse. It thus functions not only as formal evidence but also as protection for victims’ rights and a means to achieve substantive justice.